The sparkling Universe: A scenario for cosmic void motions - Ceccarelli, Maria Laura (2016)
Cosmic voids are prominent features of the Universe, encoding relevant information of the growth and evolution of structure through their dynamics. Here, we perform a statistical study of the global motion of cosmic voids using both a numerical simulation and observational data. Their relation to large-scale mass flows and the physical effects that drive those motions. We analyse the bulk motions of voids, finding void mean bulk velocities in the range 300- 400 km s-1, depending on void size and the large-scale environment. Statistically, small voids move faster, and voids in relatively higher density environments have higher bulk velocities. Also, we find large-scale overdensities (underdensities) along (opposite to) the void motion direction, suggesting that void motions respond to a pull-push mechanism. Our analysis suggests that their relative motions are generated by large-scale density fluctuations. In agreement with linear theory, voids embedded in low (high) density regions mutually recede (attract) each other, providing the general mechanism to understand the bimodal behaviour of void motions. We have also inferred void motions in the Sloan Digital Sky Survey using linear theory, finding that their estimated motions are in qualitatively agreement with the results of the simulation. Our results suggest a scenario of galaxies and galaxy systems flowing away from void centres with the additional, and more relevant, contribution of the void bulk motion to the total velocity.